“LIKE A MONKEY WITH A MINIATURE CYMBAL”: CULTURAL PRACTICES OF REPETITION IN VISUAL SOCIAL MEDIA - Highfield, Tim; Duguay, Stefanie (AoIR Selected Papers of Internet Research, 2015)
Looping media are recurring components of online content, from gifs to Vine videos, in addition to the conceptual repetition of memes and related practices. This paper analyses practices around looping visual media as examples of vernacular creativity, social media literacies, and internet culture, especially for irreverent and playful purposes. Focusing on the LGBTQ digital cultural context as a pilot study, this research examines multi-platform uses of looping media, including personal narratives through Vine videos and animated gifs on Tumblr. In addition to textual analysis of LGBTQ looping visual social media content, the study will further explore the platform context as part of the experience of looped media. The research will address how these factors may also contribute to practices of irreverence and play, both within the specific case of LGBTQ culture and internet culture more generally.